Managerial Competence of School Principals in Fostering Educational Innovation in Elementary Schools of Aceh Tamiang Regency - Junita Junita; Munawar Munawar; Saiful Bahri (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The rapid progression of education in the 21st century has increased the necessity for innovation in schools, especially at the primary level where fundamental skills are cultivated. School principals serve as pivotal agents of change, with administrative proficiency being a crucial factor in promoting sustainable educational innovation. This study examines the role of principals' managerial ability in fostering and executing innovation in public elementary schools in Aceh Tamiang Regency, Indonesia. Utilizing a qualitative descriptive methodology, data were gathered via in-depth interviews, observations, and document analysis involving principals and educators from three public elementary institutions. The results indicate that principals' managerial competence—exemplified by systematic planning, collaborative organization, consistent execution, and ongoing supervision—substantially fosters innovation in educational practices, school administration, and organizational culture. Nonetheless, difficulties pertaining to inadequate infrastructure, digital preparedness, and inconsistent teacher proficiency persist as barriers to the sustainability of innovation. The study finds that enhancing principals' managerial competency via ongoing professional development and institutional support is crucial for promoting educational innovation, especially in regional elementary school settings.